Abuelas defendiendo a sus nietas: Un caso de asesinato en el San Sebastián del siglo XVII - Intxaustegi Jauregi, Nere Jone (Avisos de Viena, 2023)
This paper examines a murder case involving the marriage of Antonio Ruiz de Salas and Ángela de Eleizalde. Two trials ensued after Ángela's murder, revealing intricate family dynamics and societal norms of the time. While Antonio claimed self-defense, alleging Ángela's infidelity, her grandmother vehemently defended her honor. Testimonies painted conflicting portraits of Ángela, reflecting societal views on female virtue. Legal proceedings traversed ecclesiastical and secular jurisdictions, highlighting power struggles between authorities. The absence of concrete evidence regarding Ángela's alleged pregnancy underscored the case's complexity. Ultimately, Antonio's conviction and sentencing to capital punishment epitomized the legal and social consequences of marital discord in 17th-century Spain.